¿Necesidad o virtud? Razones y alcances de los tratados continentales hispanoamericanos de 1856 - Reza, Germán A. De la (2014)
This article examines the origins and motivations of the Continental Treaties of 1856, and their differences from the confederative treaties concluded in Panama in 1826 and Lima in 1848. It also seeks to explain the transition from the Bolivarian cooperative approach to a vision based in the balance of powers. As a result of this process, unionism appears as a temporary move, skeptical about its own achievements.